State of Exception as Economic Policy: A Socio-Legal Analysis of the Puerto Rican Colonial Case - Jose Manuel Atiles-Osoria (Oñati Socio-Legal Series)
This article argues that the Puerto Rican colonial-economic, political and legal development has been based on the state of exception. By analyzing the Puerto Rican constitutional history and the sociopolitical events taking place after the 1980’s it shows that in PR, a double exceptionality operates: a colonial state of exception, which refers to the US’s uses of this paradigm as a colonial domination technique; and an internal state of exception, which refers to the uses of this paradigm by the Puerto Rican government as a dispositive to tackle economic and financial crises. This innovative approach portrays a more complex understanding of the state of exception, one that better portrays the intertwined relations between colonialism, economy and law.